2021
DOI: 10.3390/pathogens10111459
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the SARS-CoV-2-Mediated Alteration in the Stress Granule Protein Regulatory Networks in Humans

Abstract: The rapidly and constantly evolving coronavirus, SARS-CoV-2, imposes a great threat to human health causing severe lung disease and significant mortality. Cytoplasmic stress granules (SGs) exert anti-viral activities due to their involvement in translation inhibition and innate immune signaling. SARS-CoV-2 sequesters important SG nucleator proteins and impairs SG formation, thus evading the host response for efficient viral replication. However, the significance of SGs in COVID-19 infection remains elusive. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 83 publications
(110 reference statements)
0
11
0
Order By: Relevance
“…Prasad et al. ( 79 ) identified that mir-615-3p as potential candidates for the treatment of COVID-19 and associated manifestations. The obtained results showed that induction of interleukin-8 by SARS-CoV-2 Spike protein in bronchial epithelial IB3-1 cells was mediated by a miR-93-5p agomiR ( 80 ).…”
Section: Discussionmentioning
confidence: 99%
“…Prasad et al. ( 79 ) identified that mir-615-3p as potential candidates for the treatment of COVID-19 and associated manifestations. The obtained results showed that induction of interleukin-8 by SARS-CoV-2 Spike protein in bronchial epithelial IB3-1 cells was mediated by a miR-93-5p agomiR ( 80 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the serum of lactating mothers with type 1 diabetes, hsa-mir-26a-5p was upregulated and was shown to be significantly associated with inflammatory responses and cytokine-and chemokinemediated signaling pathways (78). Hsa-mir-124-3p and hsamir-20a-5p were also considered as potential therapeutic targets for COVID-19 in previous bioinformatics analysis (79)(80)(81)(82). Although many previous studies have suggested that these TFs and miRNAs may have important therapeutic effects, these analytical results require further experiments to confirm their validity and authenticity.…”
Section: Discussionmentioning
confidence: 99%
“…Hsa-miR-124-3p was considered a potential candidate for treating COVID-19 ( Prasad et al, 2021 ) and regulating ACE2 networks ( Wicik et al, 2020 ). Then, hsa-miR-191-5p showed an inhibitory effect on HIV-1 replication ( Zheng et al, 2021 ); it is associated with cervical lesions and can serve as a non-invasive biomarker ( Ning et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%